Essays on feeder cattle market dynamics - Kayode, Ajewole Martins (Kansas State University, 2019)
The United State has experienced a downward trend in cattle and calves marketing over the last decade. The gross income from cattle sales has been in the opposite direction of inventory recorded during this period. With changes in the cattle income over the years, it is expected that the market will be changing over time. This dissertation contains three related essays on feeder cattle market dynamics. The first essay explores spatial arbitrage opportunities in the feeder cattle markets across the United States. The second essay examines the time variation in the feeder cattle spatial market connectedness. The third essay examine the impact of the 2005 energy policy on the feeder cattle markets through a time-varying analysis. The objective of the first essay is to determine the frequency of price differences in spatial feeder cattle markets offer profitable arbitrage? The study further investigates factors determining spatial arbitrage opportunities between pairs of markets. Arbitrage opportunities are at the lowest during the winter in the higher weight categories. The higher the number of cattle head the higher the size of arbitrage opportunities available between spatial markets. This study is the first to use a time-varying transaction cost in the feeder cattle market spatial analysis. The arbitrage information here will serve as a guideline for potential investors in the feeder cattle market. The major study limitation is that livestock is not a truly homogenous product, and there are always at least minor differences in animal prices within a market. The second essay examines the degree of connectedness of the feeder cattle markets in the United States over time. Spillover index measure are applied to capture the impact of price shocks within selected feeder cattle markets on market connectedness. The essay further evaluates the influence of spatiotemporal factors that may impact the degree of market connectedness over the same period, and the impact of drought on periodic price transmission between markets. This is the first study to apply a time-varying approach to study feeder cattle market linkages at the auction level and factors influencing the variation in market connectedness. Seven major auction markets across five states are selected, three markets within the state of Kansas and four markets outside Kansas. There is variation in the level of market connectedness over the study period. Long term drought severity accounts for some of the dynamics in the feeder cattle market. The third essay examines the time path and magnitude of volatility translation across major agricultural commodities and energy markets and compares the causal relationships between pre-ethanol boom and post-ethanol boom periods. Results reveal strong evidence for time variation in the implied volatility spillover between the feeder cattle market and the energy market. Despite a high correlation between crude oil and feeder cattle volatilities in the post-ethanol boom period, the linkage between the two commodities’ volatilities is only for a short term.
Keywords: Feeder cattle; Spatial arbitrage; Market connectedness; Time-varying parameter; Implied volatility; Drought severity and coverage index